MERAWAT KESEHATAN MENTAL DAN FISIK PADA LANSIA UNTUK HIDUP SEHAT DAN BAHAGIA PADA MASYARAKAT DI DESA KARMEO, KABUPATEN BATANGHARI - anipah; Tri Wahyuni; Asmeriyani Asmeriyani; Yeyen Gustina Irawan (STIKES Garuda Putih, 2025)
Background: The elderly are an age group vulnerable to various health problems, both physical and mental. Mental health disorders can have an impact on the elderly, including reducing their ability to perform daily activities, increasing the risk of degenerative diseases, reducing independence, and thus reducing their quality of life. The importance of maintaining the mental and physical health of the elderly is a primary concern in improving their quality of life. Efforts that can be made include health education, regular physical activity, and adequate social support. Objective: This community service activity aims to increase awareness and skills in managing stress and maintaining physical health through providing education, training, and support to the elderly in maintaining mental and physical health so that the elderly can create a more productive and quality life. The material provided is counseling/education on stress management with breathing relaxation exercises (LAHARGO) to reduce anxiety/depression and to improve emotional well-being. Methods: The methods used include an educational approach (counseling), elderly exercise, and psychosocial therapy, as well as monitoring and evaluation of the program's impact on elderly health. The community service targets all 13 elderly people in Karmeo Village. Results: Evaluation results from questionnaires and interviews indicated that most seniors experienced positive benefits from the program, such as improved sleep quality, reduced stress, increased participation in social activities, and increased relaxation through LAHARGO breathing exercises. Conclusion: The outreach and education regarding the importance of maintaining mental and physical health successfully increased seniors' awareness of the importance of mental and physical balance in daily life. This community service activity successfully achieved its primary objective of increasing seniors' awareness and skills in maintaining mental and physical health. Keywords:. Elderly. Mental Health, Social Support